2018
DOI: 10.4314/tjpr.v17i6.30
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant treatment of brain metastases with whole brain radiotherapy and temozolomide protects neurocognitive function and improve quality of life

Abstract: Purpose: To study the protective effects of a combination of temozolomide (TMZ) and whole brain radiotherapy (WBT) on neurocognition, and its effect on the quality of life (QoL) in patients with brain metastasis (BM) from solid tumors, relative to WBT alone. Methods: A total of 256 BM patients were enrolled and divided into two groups treated with either WBT plus TMZ, or WBRT alone. All patients received 30 Gy WBT, with or without concomitant TMZ (75 mg/m 2 /day) during the irradiation period, and subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similarly, patients who survived more than 6 months after HA-WBRT with simultaneous integrated boost recovered to baseline scores regarding L&M performance [41]. On the contrary, performance on most cognitive tasks declined in at least 114 patients who received conventional WBRT [35, 39, 40]. L&M performance was most often affected, with 53% of the patients showing decline [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients who survived more than 6 months after HA-WBRT with simultaneous integrated boost recovered to baseline scores regarding L&M performance [41]. On the contrary, performance on most cognitive tasks declined in at least 114 patients who received conventional WBRT [35, 39, 40]. L&M performance was most often affected, with 53% of the patients showing decline [35].…”
Section: Resultsmentioning
confidence: 99%
“…L&M performance was most often affected, with 53% of the patients showing decline [35]. Moreover, the percentage of patients with declined performance increased from 19% at short-term to 35% at midterm follow-up [39]. Although group performance declined compared to both baseline and short-term follow-up when considering all 17 patients in the Onodera et al [25] cohort, improvements were observed in a subgroup of patients with a baseline BMs volume of <4.0 cm 3 and in BMs patients surviving at least 12 months [25].…”
Section: Resultsmentioning
confidence: 99%